Faktor-Faktor yang Mempengaruhi Fraudulent Financial Statement - Puadi, Ahmad; Hernawati, Nopi; Maemunah, Mey (UNISBA Press, 2024)
Abstract. This study aims to determine the effect of fraud hexagon factors on fraudulent financial statements in State-Owned Enterprises (BUMN) companies listed on the Indonesia Stock Exchange during the 2018-2022 period. This study uses a panel data regression method with sampling through purposive sampling method, and from this method 100 samples from 20 companies were selected for 5 years. The results of the research analysis show that Total Accrual to Asset (TATA), and change of directors (DCHANGE), have a positive influence on fraudulent financial statements. On the other hand, financial targets and measured using Return on Asset (ROA), ineffective monitoring and measured using BDOUT, Arrogance, which is indicated by the number of CEO photos contained in the annual report, and Collusion as measured by the number of concurrent positions of the independent board of commissioners, show no influence on fraudulent financial statements. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh faktor - faktor fraud hexagon terhadap fraudulent financial statement pada perusahaan Badan Usaha Milik Negara (BUMN) yang terdaftar di Bursa Efek Indonesia selama periode 2018-2022. Penelitian ini menggunakan metode regresi data panel dengan pengambilan sampel melalui metode purposive sampling, dan dari metode ini terpilih sebanyak 100 sampel dari 20 perusahaan selama 5 tahun. Hasil analisis penelitian menunjukkan bahwa Total Accrual to Asset (TATA), dan pergantian direksi (DCHANGE), memiliki pengaruh positif terhadap fraudulent financial statement. Di sisi lain, financial target dan diukur menggunakan Return on Asset (ROA), ineffective monitoring dan diukur menggunakan BDOUT, Arogansi, yang diindikasikan oleh jumlah foto CEO yang terdapat dalam laporan tahunan, dan Kolusi yang diukur dengan jumlah rangkap jabatan dewan komisaris independen, tidak menunjukkan pengaruh terhadap fraudulent financial statement.